Glass fiber-reinforced composites in dentistry - Safwat, Engie M. (2023)
Enormous improvements in dental materials’ manufacturing for the aim of producing durable dental materials without compromising the aesthetic properties were developed. One of the approaches that fulfill this aim is the use of reinforcing glass fibers as fillers into dental materials, typically resin polymers, in order to obtain glass fiber-reinforced composites. Glass fiber-reinforced composite offered many advantages to the dental materials though some limitations were recorded in many literature.